Preparation method and application of conductive adhesive hydrogel based on cyclodextrin
By employing a multi-component synergistic conductive adhesive hydrogel preparation method, the problems of difficulty in manufacturing complex structures and insufficient performance of existing conductive adhesive hydrogels have been solved. This method enables high-precision 3D printing and personalized manufacturing of bioelectronic devices, improves the stability and signal quality of the device-tissue interface, and possesses excellent biocompatibility and safety.
Patent Information
- Application Number
- CN202511669649.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-01-13
AI Technical Summary
Existing conductive adhesive hydrogel preparation technologies are difficult to manufacture complex or personalized three-dimensional structures, resulting in long production cycles, high costs, and difficulty in achieving integrated molding of functional structures. Furthermore, the rheological properties and material synergy of existing 3D printing inks are insufficient, leading to low resolution and poor shape fidelity of printed structures.
A multi-component synergistic approach was adopted, using water-soluble binders β-cyclodextrin, PEDOT:PSS, and PVA, along with water-soluble ionic conductive agents such as NaCl, KCl, or sodium citrate, to form a physical cross-linking network through freeze-thaw cycles. This resulted in the preparation of a hydrogel material with high electrical conductivity, strong tissue adhesion, and low Young's modulus, which was then used as a 3D printing ink.
It achieves a balance between high performance and high processability, significantly improves the stability and signal quality of the device-tissue interface, possesses excellent biocompatibility and safety, simplifies the manufacturing process, and promotes the practical application of the technology.
Smart Images

Figure CN121319404A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional bio-inks and flexible electronics, and particularly relates to the preparation method and application of conductive adhesive hydrogels based on cyclodextrin. Background Technology
[0002] Conductive adhesive hydrogels, due to their combination of conductivity and adhesion to biological tissues, show broad application prospects in biomedical devices, neural interfaces, and wearable devices. However, current fabrication technologies for conductive adhesive hydrogels mainly focus on traditional methods such as direct casting, injection molding, and molding. These methods have the following significant drawbacks: ① It is difficult to manufacture complex or personalized three-dimensional structures, limiting their application in customized bioelectronic devices; ② The molding process relies on prefabricated molds, resulting in long production cycles, high costs, and difficulty in rapid iterative design; ③ The manufactured hydrogel devices have a simple structure and cannot achieve integrated molding of functional structures (such as conductive circuits and adhesion interfaces), increasing the difficulty of subsequent integration and encapsulation.
[0003] Furthermore, 3D printing technology is considered an ideal solution for achieving programmable and customized manufacturing of structures. This technology relies on using a hydrogel precursor mixture as printing ink, depositing it layer by layer and inducing in-situ curing to ultimately form hydrogel devices with complex three-dimensional structures and specific functions. Currently, 3D printable conductive adhesive hydrogel precursor mixtures typically use polyvinyl alcohol (PVA) (or other physically cross-linked hydrogel components) as a matrix to provide molding capability, physically blended with PEDOT:PSS (or other conductive polymers). However, when using existing conductive adhesive hydrogel precursor mixtures as 3D printing inks: on the one hand, the introduction of conductive polymers often degrades the rheological properties of the ink, resulting in low resolution and poor shape fidelity of the printed structure; on the other hand, the synergistic effect between the components in a simple physically blended material system is insufficient, making it difficult to simultaneously achieve key properties such as high conductivity, strong adhesion, and low modulus, often resulting in a situation where one aspect is sacrificed for another. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention proposes a method for preparing and applying a conductive adhesive hydrogel based on cyclodextrin.
[0005] One of the above-mentioned objectives of the present invention is achieved by the following technical solution: A method for preparing a cyclodextrin-based conductive adhesive hydrogel, wherein the components required for preparing the conductive adhesive hydrogel include: a water-soluble binder, PEDOT:PSS, PVA, and a water-soluble ionic conductive agent, wherein the water-soluble ionic conductive agent is one of NaCl, KCl, or sodium citrate; the preparation method includes the following steps: Step 1: Add deionized water and PEDOT:PSS dispersion to a beaker and stir until homogeneous; Step 2: Add PVA, water-soluble ionic conductive agent, and water-soluble adhesive to the mixture formed in Step 1, and let it stand to allow the PVA particles to absorb water and swell. Step 3: Stir the mixture prepared in Step 2 under heating conditions to dissolve all components evenly and obtain the precursor mixture of hydrogel. Step 4: The precursor mixture obtained in Step 3 is subjected to freeze-thaw cycles to form a stable physical cross-linked network, thereby preparing a conductive adhesive hydrogel.
[0006] Furthermore, the water-soluble adhesive uses β-cyclodextrin, hydroxypropyl-β-cyclodextrin, or γ-cyclodextrin.
[0007] Furthermore, the precursor mixture of the hydrogel prepared in step 3 can be used as ink for 3D printing.
[0008] The second objective of this invention is achieved through the following technical solution: A conductive adhesive hydrogel is used in flexible bioelectronic devices such as flexible electrodes and wearable devices.
[0009] The advantages and positive effects of this invention are as follows: 1. Achieved a balance between high performance and high processability. This invention successfully prepared a hydrogel material with high electrical conductivity (dual electron / ion conductivity), strong tissue adhesion, and low Young's modulus through the synergistic effect of a multi-component system consisting of a water-soluble binder, PEDOT:PSS, PVA, and a water-soluble ionic conductive agent. This material overcomes the bottleneck of balancing performance and processability in existing technologies. Its precursor mixture is suitable for high-precision 3D printing, laying the material foundation for the manufacture of complex and personalized bioelectronic devices.
[0010] 2. Significantly improved the stability and signal quality of the device-structure interface. This invention leverages the adhesion mechanism and network regulation of cyclodextrin. The hydrogel forms a tight, conformal, and stable adhesion interface with the skin, effectively inhibiting displacement and detachment during use. Simultaneously, the unique ion / electron dual-conductivity network ensures low-impedance, high-fidelity transmission of electrophysiological signals at the interface, with a signal-to-noise ratio (SNR) significantly superior to commercial electrodes, providing a reliable guarantee for precision medical diagnosis. 3. Possesses excellent biocompatibility and safety in use. All components of this invention have good biocompatibility. Cytotoxicity tests have confirmed that the hydrogel has no significant cytotoxicity, supports normal cell growth and proliferation, and meets the biological requirements for long-term, safe implantation or attachment.
[0011] 4. It simplified the manufacturing process and promoted the practical application of the technology: This invention employs an aqueous processing and physical cross-linking strategy, resulting in a mild, simple, and environmentally friendly manufacturing process that avoids complex chemical synthesis and harsh processing conditions. Combined with 3D printing technology, it enables integrated, digital, and rapid manufacturing from materials to devices, significantly reducing the barriers to entry and costs associated with the fabrication of high-performance bioelectronic devices, paving the way for their large-scale application and commercialization. Attached Figure Description
[0012] Figure 1 This is a schematic diagram of the adhesion mechanism of conductive adhesive hydrogels; Figure 2 These are optical images of conductive adhesive hydrogels adhering to different materials; Figure 3 This is a bar chart showing the adhesion strength between conductive adhesive hydrogels and metals, glass, and skin under different β-cyclodextrin contents; Figure 4 This is a tensile-stress curve of conductive adhesive hydrogels with different β-cyclodextrin contents; Figure 5 This is a Young's modulus diagram of conductive adhesive hydrogels with different β-cyclodextrin contents; Figure 6 This is a cyclic tensile-stress curve of a conductive adhesive hydrogel. Figure 7 These are optical images of conductive adhesive hydrogels. Figure 8 This is a test diagram of editable parameters for conductive adhesion hydrogel precursor solutions; Figure 9 This is a conductivity test chart for conductive adhesive hydrogels; Figure 10 This is a test chart for the comfort of conductive adhesive hydrogel. Figure 11 This is a graph showing the in vitro cytotoxicity test results of a conductive adhesive hydrogel. Figure 12 The diagram shows the performance test results of conductive adhesive hydrogel as a flexible electrode: (a) Schematic diagram of the bicep curl task; (b) Comparison of electromyographic signals during the bicep curl task; (c) Comparison of RMS and SNR values of electromyographic signals; (d) Schematic diagram of the vibration interference test; (e) Comparison of electromyographic signals during the vibration interference test; (f) Quantitative data of the vibration interference test. Detailed Implementation
[0013] The structure of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that these embodiments are descriptive and not limiting.
[0014] A method for preparing a conductive adhesive hydrogel, the inventive point of which is that the components required for the preparation of the conductive adhesive hydrogel include: a water-soluble adhesive, PEDOT:PSS, PVA, and a water-soluble ionic conductive agent, wherein the water-soluble ionic conductive agent is one of NaCl, KCl, or sodium citrate; the preparation method includes the following steps: Step 1: Add deionized water and PEDOT:PSS dispersion to a beaker and stir until homogeneous; Step 2: Add PVA, water-soluble ionic conductive agent, and water-soluble adhesive to the mixture formed in Step 1, and let it stand to allow the PVA particles to absorb water and swell. Step 3: Stir the mixture prepared in Step 2 under heating conditions to dissolve all components evenly and obtain the precursor mixture of hydrogel. Step 4: The precursor mixture obtained in Step 3 is subjected to freeze-thaw cycles to form a stable physical cross-linked network, thereby preparing a conductive adhesive hydrogel.
[0015] Among them, water-soluble adhesives can use β-cyclodextrin, hydroxypropyl-β-cyclodextrin or γ-cyclodextrin, etc.
[0016] The precursor mixture of the hydrogel prepared in step 3 above can be used as ink for 3D printing.
[0017] Example: Add 6 ml of deionized water and 14 ml of PEDOT:PSS dispersion to a 50 ml beaker and stir until homogeneous. Next, weigh 4 g of PVA, 0.6 g of NaCl, and 0.5–3 g of β-CD and add them to the mixture. Let it stand for 2 hours to allow the PVA particles to absorb water and swell. Then, heat the mixture at 90°C and stir for 2 hours to ensure that all components are dissolved evenly, thus obtaining the precursor mixture of the hydrogel. Finally, freeze the precursor mixture at -20°C for 12 hours and thaw it at 4°C for 2 hours, repeating this process three times to obtain the conductive adhesive hydrogel.
[0018] The conductive adhesive hydrogel of this invention is prepared based on a multi-component synergistic mechanism. Its core lies in using a PVA hydrogen-bonded network formed by cyclic freeze-thaw cycles as a framework, precisely controlling the network structure and interfacial properties through the introduction of β-CD, and synergistically constructing a highly efficient dual conductive path with PEDOT:PSS and NaCl. Specifically, firstly, during the self-assembly of a three-dimensional physical network from a PVA aqueous solution through cyclic freeze-thaw cycles, the introduced β-cyclodextrin (β-CD) plays a crucial structural modulator role. Its abundant hydroxyl groups partially occupy the cross-linking sites of PVA molecules, and the steric hindrance effect generated by its rigid ring-shaped cavity structure effectively reduces the cross-linking density of the PVA gel framework. This structural change directly manifests as a significant decrease in the material's Young's modulus, thereby greatly improving the hydrogel's flexibility and conformal adhesion to irregular skin surfaces. Simultaneously, the hydroxyl groups on the β-CD surface can also directly form multiple hydrogen bonds with the skin, actively contributing to the interfacial adhesion strength. Building upon this, the conductive polymer PEDOT:PSS is in situ intercalated within the regulated PVA network, forming an interpenetrating network structure that provides a stable electronic pathway for charge transport. Finally, the introduced NaCl dissociates into abundant mobile ions within the system, further enhancing ionic conductivity. Furthermore, the precursor mixture of this conductive adhesive hydrogel exhibits excellent printability, endowing the material with superior customizability. Through digital design, the material's functional properties can be directly transformed into customized two-dimensional or three-dimensional gel structures, providing crucial support for the fabrication of personalized bioelectronic devices.
[0019] The conductive adhesive hydrogel prepared by this invention can be applied to flexible bioelectronic devices such as flexible electrodes and wearable devices.
[0020] like Figure 1 As shown, the outer edge of β-CD contains abundant hydroxyl functional groups. These functional groups can form strong interfacial interactions with corresponding groups in the stratum corneum of human skin, thereby significantly enhancing the intrinsic adhesiveness of the hydrogel. In addition to human skin, this hydrogel exhibits excellent universal adhesion capabilities, firmly adhering to surfaces of substrates such as glass, plastics, metals, wood, and polyimides. Figure 2 As shown. To quantitatively evaluate its adhesion performance, this invention selected three materials—metal, glass, and pigskin (as a human skin model)—for quantitative testing. The test results are as follows. Figure 3As shown, the adhesion strength of the hydrogel exhibits a significant positive correlation with the β-CD content. Notably, when the β-CD doping concentration reaches 10 wt%, the rate of increase in adhesion strength begins to slow down, indicating that the adhesion mechanism may be shifting from a single dominant mechanism to a synergistic effect of multiple mechanisms or approaching saturation. At this concentration, the adhesion strengths of the hydrogel to metal, glass, and pigskin reach 25.06 kPa, 18.15 kPa, and 12.05 kPa, respectively. When the β-CD concentration is further increased to 15 wt%, although the growth trend slows down, the adhesion strength still increases to 29.03 kPa, 23.28 kPa, and 15.21 kPa, confirming the effectiveness of β-CD as a highly efficient adhesion enhancer.
[0021] The tensile fracture curves of gel material samples with different β-CD contents were measured using an electronic universal testing machine, such as... Figure 4 As shown. The Young's modulus of the gel material with different β-CD contents was calculated based on the tensile fracture curve and the cross-sectional area of the gel material sample, as shown. Figure 5 As shown, the Young's modulus of the gel continuously decreases with increasing β-CD content. The reasons are as follows: Firstly, the outer hydroxyl groups of β-CD occupy some crosslinking sites of PVA molecules, leading to a decrease in the crosslinking density of the freeze-thaw crosslinked PVA gel backbone. Secondly, β-CD is a cyclic truncated pyramidal three-dimensional spatial structure, while PVA molecular chains exhibit a random coil morphology. Therefore, the introduction of β-CD hinders the aggregation of PVA molecular chains, thereby reducing the crosslinking density of PVA molecules. When the β-CD content is 2.5%, 5%, 7.5%, 10%, 12.5%, and 15%, the Young's moduli of the conductive adhesive hydrogel are 30.47 kPa, 24.02 kPa, 17.49 kPa, 14.58 kPa, 12.32 kPa, and 10.84 kPa, respectively. The Young's modulus of human skin is roughly in the range of 5 kPa to 30 kPa. The introduction of β-CD can tune the Young's modulus of the conductive adhesive hydrogel to within this range, which is extremely advantageous for conformal adhesion at the interface when using the conductive adhesive hydrogel as an epidermal electrode. Optical images of the 3D-printable conductive adhesive hydrogel with 10% β-CD content are shown below. Figure 7 As shown, under the action of external force, hydrogels can be bent, stretched, and knotted, and after the external force is removed, they can quickly return to their original shape without being damaged. Figure 6 Cyclic tensile tests under 60% strain conditions showed that the cumulative effect of strain was not significant after multiple loading-unloading cycles, demonstrating the feasibility of this 3D-printable conductive adhesive hydrogel as an epidermal electrophysiological electrode.
[0022] The conductivity of gel materials, such as Figure 9As shown, its conductivity decreases over time, which may be due to the loss of water from the hydrogel, leading to a reduction in the ionic conductivity pathways within the gel. The initial conductivity of the gel is 0.064 S / m. After standing at 37°C for 2 hours, its conductivity decreases to 0.056 S / m, with a change rate of less than 10%. After 5 hours, the conductivity decreases to 0.044 S / m, with a change rate of less than 20%.
[0023] The precursor solution of this conductive adhesive hydrogel exhibits excellent 3D printing adaptability. For example... Figure 8 As shown, it can achieve stable printing over a wide range of parameters, ensuring the robustness of the process. Leveraging the digital advantages of 3D printing, it can easily achieve rapid and precise prototyping from simple geometries (such as circles, rectangles, and stars) to complex functional structures (such as interdigitated electrodes). This high degree of programmability provides a powerful and flexible manufacturing platform for the development of customized flexible electronic devices.
[0024] Good biocompatibility is a prerequisite for the clinical application of gel materials. To systematically evaluate the biocompatibility of this 3D-printable conductive adhesive hydrogel, this invention comprehensively evaluated it from two aspects: skin comfort and in vitro cytotoxicity. First, in the skin comfort test, the PPCN hydrogel was attached to the flexor arm of a healthy volunteer, with a commercially available Ag / AgCl gel electrode used as a control. Figure 10 As shown, during the 5-hour observation period, neither material caused erythema, edema, itching, or other adverse reactions on the subjects' skin, indicating that the 3D-printable conductive adhesive hydrogel possesses excellent wearing comfort. Secondly, to further quantify the cytotoxicity of the material, this invention, referring to ISO 10993-5 standard, employed in vitro cytotoxicity experiments. Specifically, this invention prepared an extract of the gel and used this extract to intervene in L929 mouse fibroblasts. Cell proliferation activity was detected using the CCK-8 assay. Experimental results are as follows... Figure 11 As shown, the survival rate of L929 cells treated with this gel extract was not significantly different from that of the control group. In summary, this 3D-printable conductive adhesive hydrogel exhibits excellent biocompatibility and did not induce significant skin irritation or cytotoxicity, demonstrating its safety and reliability as a surface electrophysiological electrode.
[0025] To evaluate the application potential of conductive adhesive hydrogels as flexible electrodes, such as Figure 12As shown, conductive adhesive hydrogel electrode pairs and commercial Ag / AgCl electrodes were attached to the biceps brachii muscles of subjects, respectively, and the same bicep curl task was performed. Thanks to the low impedance and excellent conformal capability of the conductive adhesive hydrogel, the conductive adhesive hydrogel electrode pair exhibited higher amplitude and a higher signal-to-noise ratio than the Ag / AgCl electrode. While the subject's arm was at rest, vibrations of varying intensities were applied to the skin on one side of the electrode pair using a fascia gun to simulate a real-world usage scenario. Significant differences were observed between the conductive adhesive hydrogel electrode pair and the commercial Ag / AgCl electrode pair. Due to the rigid connection between the commercial Ag / AgCl electrode and the cable, the electromyographic signals acquired by the commercial Ag / AgCl electrode showed significant noise interference when vibration was applied, while the conductive adhesive hydrogel electrode was only slightly affected. These experimental results validate the significant application potential of this conductive adhesive hydrogel electrode for highly reliable physiological signal monitoring in dynamic, real-world scenarios.
[0026] Although embodiments and drawings of the present invention have been disclosed for illustrative purposes, those skilled in the art will understand that various substitutions, variations and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A method for preparing a conductive adhesive hydrogel based on cyclodextrin, characterized in that: The components required for preparing the conductive adhesive hydrogel include: a water-soluble adhesive, PEDOT:PSS, PVA, and a water-soluble ionic conductive agent, wherein the water-soluble ionic conductive agent is one of NaCl, KCl, or sodium citrate; the preparation method includes the following steps: Step 1: Add deionized water and PEDOT:PSS dispersion to a beaker and stir until homogeneous; Step 2: Add PVA, water-soluble ionic conductive agent, and water-soluble adhesive to the mixture formed in Step 1, and let it stand to allow the PVA particles to absorb water and swell. Step 3: Stir the mixture prepared in Step 2 under heating conditions to dissolve all components evenly and obtain the precursor mixture of hydrogel. Step 4: The precursor mixture obtained in Step 3 is subjected to freeze-thaw cycles to form a stable physical cross-linked network, thereby preparing a conductive adhesive hydrogel.
2. The method for preparing the conductive adhesive hydrogel based on cyclodextrin according to claim 1, characterized in that: The water-soluble adhesive uses β-cyclodextrin, hydroxypropyl-β-cyclodextrin, or γ-cyclodextrin.
3. The method for preparing the conductive adhesive hydrogel based on cyclodextrin according to claim 1, characterized in that: The precursor mixture of the hydrogel prepared in step 3 can be used as ink for 3D printing.
4. An application of a hydrogel prepared using the method for preparing a cyclodextrin-based conductive adhesive hydrogel according to claim 1 or 2, characterized in that: Applications of the conductive adhesive hydrogel in flexible electrodes and bioelectronic devices in wearable devices.